2016
DOI: 10.1080/01616412.2016.1250459
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal steroids block the calpain-1-dependent intrinsic pathway of apoptosis in an experimental rat stroke model

Abstract: We conclude that a combined steroid treatment inhibits ischemia-induced neuronal apoptosis through the regulation of intrinsic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…As far as is known, apoptosis plays a decisive role in mediating cell death through two major signaling pathways: the intrinsic pathway mediated by Cyto C release from mitochondria to stimulate caspase‐9, and the extrinsic apoptotic pathway originating from the activation of cell surface death receptor (DR) and stimulating caspase‐8 . Therefore, the activities of Caspase‐3, ‐8, and ‐9 in the cells was determined in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as is known, apoptosis plays a decisive role in mediating cell death through two major signaling pathways: the intrinsic pathway mediated by Cyto C release from mitochondria to stimulate caspase‐9, and the extrinsic apoptotic pathway originating from the activation of cell surface death receptor (DR) and stimulating caspase‐8 . Therefore, the activities of Caspase‐3, ‐8, and ‐9 in the cells was determined in this study.…”
Section: Resultsmentioning
confidence: 99%
“…As far as is known, apoptosis plays a decisive role in mediating cell death through two major signaling pathways: the intrinsic pathway mediated by Cyto C release from mitochondria to stimulate caspase-9, and the extrinsic apoptotic pathway originating from the activation of cell surface death receptor (DR) and stimulating caspase-8. 21 Therefore, the activities of Caspase-3, -8, and -9 in the cells was determined in this study. The results showed that the activities of Caspase-3 (7.04 ± 0.61), Caspase-8 (10.92 ± 1.31), and Caspase-9 (8.87 ± 0.73) in Ad-PLCγ2 shRNA transfected group were lower than that those the blank control and Ad-dull groups, with significant difference (P < 0.05).…”
Section: Plcγ2 Silncing Inhibits Cell Apoptosis Through Extrinsic and Intrinsic Pathwaysmentioning
confidence: 99%
“…Infarct size. as described in previous studies (22,23), after reperfusion for 48 h, the animals were anesthetized by intraperitoneal injection of 10% chloral hydrate (400 mg/kg) and then decapitated. The brain was rapidly removed, and the coronal section of brain was sliced in a special groove (thickness: 2 mm) after cooling in ice-cold saline for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Although used extensively in stroke research, there is limited knowledge of how TTC-treated rat brain sections are altered and if they can be used for quantitative immunohistochemical detection after staining with TTC. Regardless, several studies have used TTC stained brain sections for immunohistochemical studies [7, 8] and quantification of proteins using fluorescence intensity [4, 9–12] without considering the potential effects of TTC on the immunohistochemical composite staining, including autofluorescence, nonspecific secondary antibody fluorescence, and primary antibody detection. Thus, we investigated whether TTC-treated rat brain sections were altered and if they could be used for quantitative immunohistochemical detection.…”
Section: Introductionmentioning
confidence: 99%